THE EFFECT OF RELIGIOSITY, SOCIAL ENVIRONMENT, AND GOVERNMENT SUPPORT ON THE INTENTION OF MSMEs TO SAVING AT ISLAMIC BANK IN MALANG CITY - Dewi Nurjannah; Imam Mukhlis; F. Danardana Murwani (International Journal of Economy, Education and Entrepreneurship, 2023)
The purpose of this study is to find out the factors that influence the decline in customers who save at Islamic banks. This research was built to study the relationship between religiosity, social environment, and government support on the intention of MSMEs to save at the Islamic Bank in Malang City. This study took three independent variables, namely religiosity, social environment, and government support, and one dependent variable on intention to save. The grand theory uses the Theory of Planned Behavior (TPB). This research is a quantitative study using a questionnaire. The data used in this study is primary data from a sample of MSMEs who have a bank account and have plans to open a savings account at the Islamic Bank in Malang. This study uses a sampling technique accidental sampling. Respondents in this study were 140 respondents. This study uses SmartPLS 3.3.2 to process data to find answers to hypotheses. The results of this study conclude that religiosity and social environment affect the intention of MSMEs to save at an Islamic bank in Malang City, but government support gives different results where government support does not affect the intention to save at the Islamic bank in Malang City this study focuses on internal and external factors that affect the intention MSMEs to saving at Bank Islamic in Malang City